The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1590/s0071-12761976000100031
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do controle químico do Aspergillus flavus e produção de aflátoxina no amendoim (Arachis hypogaea L.) no campo

Abstract: No presente trabalho foi estudada a possibilidade de controle da produção de aflatoxina pelo Aspergillus flavus em amendoim, pela aplicação de fungicidas sobre as vagens logo após seu arran¬ camento. Quatro fungicidas eficientes selecionados previamente em testes "in vitro" (Ferbam, Thiram, Ortofenilfenato de sódio e Captaiol) foram utilizados em experimentos levados a efeito durante quatro anos nas regiões de Caiabu, Campinas, Marília, Pirapozinho e Ribeirão Preto.Os resultados levaram à conclusão, dentro do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1995
1995
1995
1995

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…They concluded that A. flavus growth and aflatoxin production could be eliminated by post-harvest treatment of the peanuts with some chemicals sprayed on to peanut pods under field conditions. Field studies, spraying peanuts with some fungicides, were conducted in Brazil, by Fonseca et al (1976Fonseca et al ( ,1992. The results showed the impossibility of reaching a sound conclusion about the substances' efficiency because of difficulties found in field applications.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that A. flavus growth and aflatoxin production could be eliminated by post-harvest treatment of the peanuts with some chemicals sprayed on to peanut pods under field conditions. Field studies, spraying peanuts with some fungicides, were conducted in Brazil, by Fonseca et al (1976Fonseca et al ( ,1992. The results showed the impossibility of reaching a sound conclusion about the substances' efficiency because of difficulties found in field applications.…”
Section: Introductionmentioning
confidence: 99%
“…(KIMATI, 1978;SMITH & MOSS, 1985;SALUNKE & DESAI, 1986). Sua eficiência também foi comprovada in vitro contra Aspegi77us f7avus na dose de 20 g/litro (FONSECA et al, 1976 (MILWARD, 1976;AZZOUZ & BULLERMAN, 1982;LENNOX & McELROY, 1984;MAGAN & LACEY, 1986;FIORENTIN & BARIONI, 1991). Os estudos in vitro têm demonstrado ainda, que as doses são dependentes do pH, ou seja, o efeito inibidor do ácido é maior à medida que o pH decresce (TSAI et al, 1984;MAGAN & LACEY, 1986;MARSHALL & BULLERMAN, 1986;RUSUL et al, 1987).…”
Section: Discussionunclassified